Reconstructing the Application of Denda Damai (Settlement-by-Fine Mechanism) in Corruption Cases: A Socio-Legal and Cultural Perspective in Indonesia - Adi Setya Desta Landya; Aida Dewi (Journal of Law, Society and Living Norms, 2025)
The growing discourse on the application of denda damai (settlement-by-fine mechanism) as an alternative approach to corruption cases reflected a shifting orientation in Indonesian law enforcement from retributive punishment toward administrative efficiency and restorative considerations. This study employed a normative legal method supported by a socio-legal perspective to evaluate whether this mechanism could be normatively justified and socially accepted when applied to corruption, which is legally classified as an extraordinary crime. The analysis showed that, although the settlement-by-fine mechanism offered potential administrative efficiency and faster recovery of state losses, it conflicted with the Anti-Corruption Law, which explicitly stated that restitution did not eliminate criminal liability. The findings also demonstrated strong public resistance rooted in cultural expectations of punitive justice toward corruption offenders. This study concluded that any policy reform in this area required normative consistency, procedural safeguards, and cultural legitimacy to align restorative aspirations with Indonesia’s prevailing legal and social values.